2000
DOI: 10.1016/s0190-9622(00)90168-3
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 and IgE are the major immunoglobulins targeting the NC 16A domain of BP 180 in bullous pemphigoid: Serum levels of these immunoglobulins reflect disease activity

Abstract: Our data demonstrate that remission of BP is paralleled by a decrease of serum levels of IgE and the different IgG subclasses reactive with BP180 NC16A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 35 publications
0
13
2
Order By: Relevance
“…Furthermore, anti-BP180-NC16A IgG subclasses were identical between healthy blood donors and BP patients (Table 3 ). Our result that no IgG4 anti-BP180-NC16A antibodies were detected in BP patients seemingly contradicts a previous report [ 33 ], although it might be due to the small number of BP serum samples included in our current study. In addition, the fine mapping of the autoantibody response in our samples revealed differences in the cohort of healthy blood donors compared to BP patients (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Furthermore, anti-BP180-NC16A IgG subclasses were identical between healthy blood donors and BP patients (Table 3 ). Our result that no IgG4 anti-BP180-NC16A antibodies were detected in BP patients seemingly contradicts a previous report [ 33 ], although it might be due to the small number of BP serum samples included in our current study. In addition, the fine mapping of the autoantibody response in our samples revealed differences in the cohort of healthy blood donors compared to BP patients (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Previously, we and others proposed a relationship between circulating total IgE [1], [37], [50], or BP180 specific IgE [37], [40], [51], [52], and the severity of clinical BP. Additionally, there is evidence for eosinophil degranulation in lesional tissue [22], [26] and, recently, we have shown that peripheral eosinophil numbers more accurately reflect disease activity than IgG autoantibody levels [53].…”
Section: Discussionmentioning
confidence: 99%
“…Autoallergic mast cell activation has been implied to play a role in other chronic inflammatory skin disorders such as atopic dermatitis [17], [18] and bullous pemphigoid [19], [20], [21]. In both diseases IgE antibodies directed to skin antigens have been described and may play a role in the pathogenesis by activating cutaneous mast cells after binding their corresponding skin antigen.…”
Section: Discussionmentioning
confidence: 99%